Body composition during the first 4 months in infants affected by neonatal abstinence syndrome: a pilot study. (2nd February 2022) - Corr, Tammy E.; Schaefer, Eric W.; Paul, Ian M.
Abstract: Newborns with neonatal abstinence syndrome (NAS) display symptoms related to neurologic excitability and autonomic dysfunction that result in increased metabolic demands. These infants also exhibit feeding difficulties and/or hyperphagia. Because the effects of these symptoms and behaviors on growth are unknown, we sought to measure serial body composition measurements over the first 4 months in infants with NAS requiring pharmacologic treatment using air displacement plethysmography. Fourteen infants of singleton birth with appropriate-for-gestational-age (AGA) weight and a gestational age of ≥35 weeks and <42 weeks were evaluated. In mixed-effects models, per week, infants increased in mean fat percent by 1.1% (95% confidence interval [CI]: 0.85–1.43), fat mass by 90 g (CI: 70–100), and fat-free mass by 140 g (CI: 130–150). The subgroup of infants ( N = 5) requiring multidrug therapy for symptom control had lower mean fat percent (−1.2%, CI: −5.2–2.1), fat mass (−60 g, CI: −25–13), and fat-free mass (−270 g, CI: −610–80) across time compared to infants requiring monotherapy. We are the first to report how body composition measures change over time in a small group of patients with NAS. Infants with NAS were smaller and leaner in the first several weeks compared to previously reported body composition measurements in term infants, but grew similarly to their healthy counterparts by 16 weeks. Infants with more severe NAS may be at risk for abnormalities in longer term growth.